CULTIVATION OF OYSTER MUSHROOM (Pleurotus spp.) USING FERMENTATION SUBSTRATE - Nguyễn Hoàng Mai; Trương Bình Nguyên; Phan Hoàng Đại; Lê Bá Dũng (Tạp chí Khoa học Đại học Đà Lạt)
This study was carried out on the cultivation of five species of Pleurotus using fermentation substrate. Paddy (Oryza sativa) was used for spawn production. Five species of Pleurotus (identified and selected in the isolation process from mushroom farms in Lamdong province) with prepared compost were examined for time of spawn running, infection rate and biological efficiency. The experiment was set up as a completely randomized design with three replicates. Pleurotus hybrid (P. hybrid) and Pleurotus sajor-caju (P. sajor-caju) had good growth potential on compost. It took about 21 days for the mycelium to spread completely through the substrate (5kg per bag). However, P. abalonus, P. citrinopileatus, and P. djamor did not grow well on fermentation substrate. In this study, although the inoculation was not conducted under sterile conditions, fungal infections were not present (0%) and the biological efficiency exceeded 62% (P. hybrid attained 62.68 ± 9.13% and P. sajor-caju 62.82 ± 7.56%).